Is the existence of God reasonable? - Martino, Eva (Advances in Social Sciences Research Journal, 2020)
In this article the question of whether the existence of God is reasonable will be addressed. The start point will be the debate between Dr. Craig and Dr. Rosenberg that took place in 2013 around the question “Is faith in God reasonable?” This debate has been chosen for being representative of general theist and atheist positions. The former usually believe in God first, and then try to formulate arguments that can help them transmit their faith to others, whereas atheists usually find arguments first that they consider illogical or incoherent related to the existence of God, and in a second moment they come to reject faith. It will be analyzed following the pragma-dialectical approach defined by Van Eemeren and Grootendorst, that considers argumentation as a speech act that aims to solve a difference in opinion. This analysis will show the main obstacles that prevented the speakers to arrive to an understanding, mainly a different vision of God and the goal that they were seeking.